2020
DOI: 10.9734/jamcs/2020/v35i530283
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Mathematical Model for the Antimalarial Activity of Methanolic Root Extract of Azadirachta indica (Dongoyaro) in Mice Infected with Plasmodium berghei NK65

Abstract: The study determines the experimental and mathematical model for the anti-plasmodial activity of methanolic root extract of Azadirachta indica in Swiss mice infected with Plasmodium berghei NK65. Phytochemical analyses, antimalarial activity of the methanolic root extract of A. indica was determined in mice infected with Plasmodium berghei NK65 using standard procedure. Liver biomarker enzymes were also determined. The model P. berghei induced free and P. berghei infected equilibrium were determined. The stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A mechanistic study has revealed that alkaloids arrest cell division, thus inhibiting cancer proliferation [54]. Adeniyi et al [4] study shows that A.indica methanolic root extract contain secondary metabolite like phenolic compunds, flavonoids, alkaloids, saponins, tannin etc. Manda et al [55] study shows that A.indica methanolic root extract possess carbohydrate, flavonoids, alkaloids, phenolic compound, saponins, tannin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mechanistic study has revealed that alkaloids arrest cell division, thus inhibiting cancer proliferation [54]. Adeniyi et al [4] study shows that A.indica methanolic root extract contain secondary metabolite like phenolic compunds, flavonoids, alkaloids, saponins, tannin etc. Manda et al [55] study shows that A.indica methanolic root extract possess carbohydrate, flavonoids, alkaloids, phenolic compound, saponins, tannin.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomic classification of Azadirachta indica (neem) include: Order; Rutales, Suborder; Rutinae, Family; Meliaceae, Subfamily; Melioideae, Tribe; Melieae, Genus; Azadirachta, and Species indica" [3]. Numerous studies have shown different biological and pharmacological activities of Azadirachta indica which include antimalarial, anti-inflammatory, antiarthritic, antioxidant and free radical scavenging activities, antipyretic, hypoglycemic, antibacterial, antigastric ulcer, antifungal and antitumour activities [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%